2022
DOI: 10.1186/s12872-022-02954-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of metabolic disorders on short- and long-term mortality after coronary artery surgery in the elderly

Abstract: Background Elderly patients undergoing cardiac operation often suffer various metabolic comorbidities, such as diabetes mellitus (DM) and obesity. The metabolic disorders in these individuals are widely considered to be possible predisposing factors for unfavourable prognosis. This retrospective study was aimed to determine the association of metabolic diseases with the mortality of elderly patients after coronary artery bypass grafting (CABG) and to identify the protective or risk factors rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…They suggested that this mortality reduction may be limited to appendicular surgery or orthopaedics, as increased adiposity may have a less profound effect relative to operations involving the abdominal or thoracic cavity. However, multiple studies report similar findings in cardiac surgery, 49–51 suggesting the obesity paradox extends beyond the musculoskeletal system. Our findings indicate that an underlying physiological difference in obese patients, both with and without MetS, is responsible for this reduced mortality.…”
Section: Discussionmentioning
confidence: 82%
“…They suggested that this mortality reduction may be limited to appendicular surgery or orthopaedics, as increased adiposity may have a less profound effect relative to operations involving the abdominal or thoracic cavity. However, multiple studies report similar findings in cardiac surgery, 49–51 suggesting the obesity paradox extends beyond the musculoskeletal system. Our findings indicate that an underlying physiological difference in obese patients, both with and without MetS, is responsible for this reduced mortality.…”
Section: Discussionmentioning
confidence: 82%